Enhancing livelihood strategies of rural communities prone to climate risk in the Caprivi Region of Namibia - Nyambe, Jacob Mulele (University of Limpopo (Turfloop Campus), 2013)
Declining rural livelihood and coping strategies in the Caprivi region have for some time been blamed on climate risk factors alone. Prominent climate risk factors are drought and floods. While the indignation of many speculators about the devastating effects of climate risk factors on annual harvests may be valid, the truth is that there are now new constraints on the livelihoods of rural households. Multi-stage cluster and stratified random sampling were used in identifying respondents. Data was collected by means of face-to-face interviews with a structured questionnaire that was applied on a sample of 253 respondents. The respondents resided in three constituencies, namely Kabbe, Katima Rural and Linyanti, which are classified as floodplains. With regards to the analytical framework, the thesis used descriptive statistics, factor analysis, a logistics regression model, as well as an unconstrained multivariate regression model. The objective of the thesis is to suggest mitigating strategic policy prescriptions that will enhance the livelihoods of rural communities in the Caprivi region. The results revealed that albeit agriculture is the main livelihood strategy, it is on a declining path in the context of livestock numbers (cattle, goats and chickens) and crop harvest (maize, millet and sorghum). Of the respondents, a substantial number (31%) of rural households are headed by people who are ≥ 56 years of age. Notwithstanding the damage caused to crop fields by other factors, the main causative factor to the poor harvest in 2007 was wild animals. The biannual harvesting approach has been abandoned for a single approach owing to climate risk factors and changes in the natural environment attributed to climate change and destruction of crop field by wild animals. The average annual rainfall at Katima Mulilo is 653 mm, but volatility in annual rainfall often results in drought or floods. Malaria, Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome are to blame for reduced availability of labour to maintain livelihood activities that sustain rural households. The results further show that five factor components make rural households eligible for receiving food aid. The first is the capacity to farm, the second is climate risk awareness, the third is household economic status, the fourth is past economic opportunities, and the last factor is household labour fitness. Salient to a rural farming household’s decision to farm are three variable, namely food cost, age of the head of the household and the value of food aid. Using income as a proxy to the de factor inadvertent climate risk occurrences and damage to crops by wild animals, pension in the hands of heads of rural households, the value of livestock owned by rural households and, the value of food aid provided to rural households proved to have a significant relationship with rural household income. In order to enhance rural livelihoods in the study area, the government and development partners should work towards establishing a repository for indigenous knowledge which rural communities have employed in the past. This knowledge should be improved on in order to use it in tackling related challenges in future. There is a need to invest more in agricultural infrastructure such as water-catchment facilities and irrigation infrastructure to assist communities to embark on irrigated vegetable farming in dry seasons; establish health facilities close to rural communities that are remote; address the lack of access to finance in the study area; and as an illustration of the lack of government projects in the study area, the green scheme should be rolled out in the area. The opening up of conservancies in areas where rural communities eke out their living from the agricultural livelihood strategy has caused unintended consequences for farming rural households. Thus the policy interface gap between the opening up of community conservancies and the agricultural policy affecting the agricultural livelihood strategy need to be addressed.
Thesis (PhD. (Agricultural economics)) --University of Limpopo, 2013
Keywords: Climate changes; Climate risk factors; 333.73; Climate changes; Risk management -- Namibia; Rural conditions -- Namibia